Spatial and historical patterns of sedimentary organic matter sources and environmental changes in the Ross Sea, Antarctic: implication from bulk and n-alkane proxies - Yang, Dan; Chen, Wenshen; Huang, Wenhao; Zhang, Haisheng; Han, Zhengbing; Lu, Bing; Zhao, Jun (Frontiers in Marine Science, 2024)
Organic carbon (OC) burial in the Antarctic marginal seas is essential for regulating global climate, particularly due to its association with ice shelf retreat. Here, we analyzed total OC (TOC), total nitrogen (TN), radiocarbon isotope, n-alkanes and relative indicators in surface and core sediments from the Ross Sea, West Antarctica. Our aim was to investigate spatial and historical changes in OC sources, and to explore the influencing factors and implications for ice shelf retreat since the last glacial maximum (LGM). Our results revealed distinct spatial patterns of OC sources as indicated by n-alkane indicators in surface sediments. In the Western Ross Sea, n-alkanes predominantly originated from phytoplankton and bacteria, as evidenced by their unimodal distribution, low carbon preference index (CPI) of short-chain n-alkanes (CPIL = 1.41 ± 0.30), and low terrestrial/aquatic ratio (TAR = 0.22 ± 0.14). In the Southwest Ross Sea, n-alkanes were derived from marine algae and terrestrial bryophytes, indicated by bimodal distribution, low ratio of low/high molecular-weight n-alkanes (L/H = 0.62 ± 0.21), low CPI of long-chain n-alkanes (CPIH = 1.18 ± 0.16), and high TAR (1.26 ± 0.66). In contrast, the Eastern Ross Sea exhibited n-alkanes that were a combination of phytoplankton and dust from Antarctic soils and/or leaf waxes from mid-latitude higher plant, as suggested by both unimodal and bimodal distributions, high L/H (1.60 ± 0.58) and CPIH (2.04 ± 0.28), and medium TAR (0.61 ± 0.30). Geologically, during the LGM (27.3 – 21.0 ka before present (BP)), there was an increased supply of terrestrial OC (TOC/TN = 13.63 ± 1.29, bimodal distribution of n-alkanes with main carbon peaks at nC17/nC19 and nC27). From 21.0 to 8.2 ka BP, as glaciers retreated and temperatures rose, the proportion of marine n-alkanes significantly increased (TOC/TN = 9.09 ± 1.82, bimodal distribution of n-alkanes with main carbon peaks at nC18/nC19 and nC25). From 8.2 ka BP to the present, as the ice shelf continued to retreat to its current position, the marine contribution became dominant (TOC/TN = 8.18 ± 0.51, unimodal distribution of n-alkanes with main carbon peak at nC17/nC18/nC19, and low TAR (0.41 ± 0.32)). This research has significant implications for understanding the variations in Antarctic OC sources and their climatic impacts in the context of accelerated glacier melting.